DIFFICULTIES, CHALLENGES AND STRATEGIES IN TEACHING ENVIRONMENTAL EDUCATION TROUGH DEALING SOME ENVIRONMENTAL PROBLEMS (2015)
In issue of educational practice carried out in ied Tomás Carrasquilla and the developing of a research project around Environmental Education as a line of research in Colombian Educational Contexts from the Universidad Pedagogica Nacional (upn) Biology Department. The teaching strategy was developed in three workshops from February 15 to November 05 of 2014, with students (42) of 10-01JM grade; the research was interpretative approach and had a qualitative methodology. Its objective is to question the difficulties, challenges and strategies in teaching environmental education (EA) through dealing some environmental problems. The results of research approach the difficulties in teaching EA are focused in the reduction of theoretical-practice field, the educational model for the sustainable development, the emergence of collectivework in classes and the view of environmental problems as isolated processes of the subjects immersed in the culture and environment; the challenges are focused on the training of teachers committed to social transformation, the environmental education as a pedagogical practice field, the trans disciplinary work and the understanding of the country realities; whit that the strategies are part of the opportunity as educators, we have of move the rooms in to take decisions ethical and committed with the socioenvironmental realities.